A circularly polarized antenna integrated with a solar cell metasurface for cube sat - Ta, Son Xuat; Park, Ikmo (Asia-Pacific Microwave Conference Proceedings, APMC, 2018)
A low-profile, broadband, circularly polarized (CP) antenna integrated with solar cells is proposed for use in CubeSats. The antenna is a single-feed printed crossed-dipole radiator on a metasurface reflector that consists of a lattice of square solar cells mounted on a grounded dielectric substrate. The radiator is designed to allow 100% insolation of the solar cells when directly facing a light source. The metasurface is used as an artificial reflector of the crossed dipole to achieve a low-profile as well as broadband characteristics. The low-profile design could also minimize shadowing of the solar cells for oblique angle insolation. The final prototype with an overall size of 100 mm × 100 mm × 5.9 mm (0.75λo × 0.75λo × 0.044λo at 2.25 GHz) yields a |S11| < -10 dB bandwidth of 2.02-2.58 GHz and a 3-dB axial ratio bandwidth of 2.12-2.44 GHz. The antenna radiated a good broadside right-hand CP wave with a high broadside gain and high radiation efficiency within the operational bandwidth.
Keywords: Cell-be; Cell/B.E; Cell/BE; Circularly polarized antennas; Crossed dipoles; Cube sat; Cubesat; Integrated antennas; Low-profile; Metasurface; Circular polarization; Crossed dipole; CubeSat; Insolation; Integrated antenna; Metasurface; Solar cell